The First Genomic Characterization of the Chikungunya Virus in Saudi Arabia - Hassan I. Alguridi; Faisal Alzahrani; Hisham N. Altayb; Safar Almalki; Eitezaz Zaki; Saeed Algarni; Abdullah Assiri; Ziad A. Memish (Springer, 2023)
Abstract Background Chikungunya is an arboviral infection caused by the Chikungunya virus (CHIKV) transmitted to humans by mosquitoes of Aedes spp. CHIKV has been confined to African countries and South-East Asia up to 2004, but since then, the pathogen has become more global, and its high morbidity rate has become more visible. Saudi Arabia is not an endemic region of CHIKV, and the virus's origin is not yet fully understood. This study aimed to characterize the genome of CHIKV from samples detected in Jeddah in 2018. Method Twenty-two sets of primers were designed to amplify near-full length genome of CHIKV. RT-PCR was conducted from clinical samples. Two samples were used for studying near complete genome sequence while the remaining samples were used to study the E1 gene. Different bioinformatics tools were utilized. Results Phylogenetic analysis showed that the CHIKV strains clustered with strains isolated from Kenya during 2017-2018 and belonged to ECSA genotype. E1: L136F, K211E and I317V mutations were identified in our strains. Also, E2: M74I, A76T, and V264A mutations were documented. Additionally, the capsid N79S substitution was also detected. Conclusion The genome of CHIKV was analyzed for the first time in Saudi Arabia to better understand the origin of the CHIKV and its genetic diversity, which showed high similarity with IE-a subclade of CHIKV strains detected in Mombasa (Kenya) indicating its possible origin.